PENGGUNAAN SOFTWARE CABRI 3D DALAM PEMBELAJARAN MATEMATIKA UPAYA MENINGKATKAN KEMAMPUAN VISUALISASI SPASIAL MATEMATIS SISWA - Alpha Galih Adirakasiwi; Attin Warmi (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
The purpose of this study was to improve the mathematical spatial visualization ability of SMK (vocational high school) students through learning with Cabri 3D software on space geometry material. The study used quasi experimental method with posttest control group design. Experiments were conducted in two classes each used learning with Cabri 3D software, and conventional learning. The population used in this study was the students of class XI TKJ 2 SMK Rosma with 30 students as samples. Data collection techniques used in this study included spatial visualization ability test, the observation of students dan teachers’ activities, and students’ response questionnaire to learning with Cabri 3D software. The results of data analysis showed that learning used Cabri 3D software provided an improvement to the ability of mathematical spatial visualization on space geometry material. Learning with 3D cabri software had a positive impact between students’ activities and students' mathematical spatial visualization.